Synthesis and characterization of poly(benzimidazolium) membranes for anion exchange membrane fuel cells - Lee, Hye-Jin; Choi, Jieun; Han, Jun Young; Kim, Hyoung-Juhn; Sung, Yung-Eun; Kim, Hwayong; Henkensmeier, Dirk; Cho, Eun Ae; Jang, Jong Hyun; Yoo, Sung Jong (Springer Verlag, 2013)
Poly(dimethyl benzimidazolium) iodides were synthesized from polybenzimidazole derivatives by permethylation. They were easily changed to OH-, CO3 (2-) and HCO3 (-) ion conducting electrolytes by immersing in 1 M of KOH, K2CO3 and KHCO3. Properties of polymers were changed by the ion exchange process. The anion conducting membranes showed tough and flexible properties. The water uptake, ion exchange capacity and conductivity varied depending on the counter anions. One of the poly(dimethyl benzimidazolium) carbonate membranes, Me-DAB-OBBA-carbonate showed the highest water uptake (59 %) as well as ion conductivity (33.74 mS/cm at 80 A degrees C), and could be a good candidate for an anion exchange membrane for anion exchange membrane fuel cells.